2013
DOI: 10.2147/dmso.s43545
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abdominal obesity in Abia State, Nigeria: results of a population-based house-to-house survey

Abstract: Background and objectiveAbdominal obesity is associated with the risk of developing disorders, such as diabetes and hypertension. The objective of this study was to investigate the prevalence of abdominal obesity in Abia State, Nigeria.Materials and methodsWe carried out a cross-sectional study aimed at ascertaining the prevalence of abdominal obesity in Abia State, Nigeria. Participants in the study were recruited from communities in the three senatorial zones in the state. Screening for abdominal obesity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 24 publications
(26 reference statements)
10
37
2
1
Order By: Relevance
“…This study showed that increasing age was associated with greater odds of being obese, a finding that is consistent with a previous study in Nigeria, (Chukwuonye et al, 2013). This is also in keeping with the fact that central obesity increases with age as indicated in this study.…”
Section: Predictors Of Central Obesitysupporting
confidence: 93%
See 3 more Smart Citations
“…This study showed that increasing age was associated with greater odds of being obese, a finding that is consistent with a previous study in Nigeria, (Chukwuonye et al, 2013). This is also in keeping with the fact that central obesity increases with age as indicated in this study.…”
Section: Predictors Of Central Obesitysupporting
confidence: 93%
“…Similar to previous local studies, both generalized and central obesity were more prevalent among the female population in the current study (Oladapo et al, 2010;Adediran et al, 2012;Iloh et al, 2012;Ahaneku et al, 2011;Adienbo et al, 2012;Desalu et al, 2008;Chukwuonye et al, 2013). A similar trend was reported by WHO (2008).…”
Section: Prevalence Of Obesitysupporting
confidence: 91%
See 2 more Smart Citations
“…[1][2][3] It is a medical problem in which excess fat has accumulated in the abdomen to the extent that it may have an adverse effect on health and/or increase medical problems. [1,2] It was once thought the health problem of affluent advanced countries but now exists in Nigeria in varying prevalence ranges [1][2][3]5] and has been described as a time bomb for the future explosion in the frequency of cardiovascular disease and metabolic syndrome. [1,4,5] Globally, in the past, abdominal obesity was viewed as a sign of wealth and wellness.…”
Section: Introductionmentioning
confidence: 99%